2020
DOI: 10.7441/joc.2020.03.02
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Consequences of Trust and Distrust in Knowledge-Intensive Organizations

Abstract: Studies measuring workplace trust in connection with leadership style and leader responsibility have become more and more important in recent years. Interest in the subject has been rising along with the recent introduction of knowledge management systems (KMSs), which has shown to be one of the most important factors of competitiveness. The aim of this research was to examine to what extent leaders of organizations are concerned about the presence of trust and/ or distrust, as well as about the economic conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…In the literature, farmers' commitment to the trading relationship is positively linked with participating in contract farming. Trust in a trading relationship is an asset that creates benefit (Bencsik et al, 2020;Gorb, 2017;Masuku & Kirsten, 2004;Tarí et al, 2020). On the other hand, trust helps in reducing performance uncertainty and plays a vital role in a relational transaction (Alkhurshan & Rjoub, 2020;Li & Nicholls, 2000).…”
Section: Relationship Qualitymentioning
confidence: 99%
“…In the literature, farmers' commitment to the trading relationship is positively linked with participating in contract farming. Trust in a trading relationship is an asset that creates benefit (Bencsik et al, 2020;Gorb, 2017;Masuku & Kirsten, 2004;Tarí et al, 2020). On the other hand, trust helps in reducing performance uncertainty and plays a vital role in a relational transaction (Alkhurshan & Rjoub, 2020;Li & Nicholls, 2000).…”
Section: Relationship Qualitymentioning
confidence: 99%
“…Nevertheless, KM authors began to focus on understanding the human factors, processes, context and interactions in knowledge creation (Bencsik et al , 2020; Jakubik, 2007, 2011; Nonaka et al , 2008, 2014; Nonaka and Takeuchi, 2011; Nonaka and Toyama, 2002; Serenko, 2013, 2021; Serenko and Bontis, 2017, 2021; Vasconcelos, 2021). Since year 2000, Nonaka et al (2008) demonstrated the importance of practical wisdom ( phronesis ) and wise leadership in KM.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding topics in KM, he concluded that there “was a noticeable increase in some topics, such as the intellectual core of the KM field; productivity and impact studies; and collaboration patterns”. For example, the economic consequences of trust and distrust in knowledge-intensive organisations (Bencsik et al , 2020), and the importance of human values and human interactions in KM research. Furthermore, Vasconcelos (2021) proposed the wisdom capital concept, which is highly relevant to KM, and presented his two-level model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust is considered as an important factor in cooperation between two or more partners (Fulmer & Gelfand, 2012) including institutional trust (Alkhurshan & Rjoub, 2020;Bencsik et al, 2020;Çera, Meço, et al, 2019;Civelek et al, 2019). It is an essential determinant of a successful buyer-seller relationship (Batt, 2000;Piricz, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%